Otherwise Healthy 15-Month-Old With Rapid-Onset Soft Tissue Swelling. Issue 8 (August 2019) - Anderson, Julie Jelaine; Avendano, Pablo; Kaila, Rahul
Abstract : Abstract: Necrotizing soft tissue infections are a serious medical emergency that involve necrosis within the soft tissue space including the dermis, subcutaneous tissue, superficial fascia, deep fascia, and muscle. Inciting factors include recent varicella infection, omphalitis, trauma, intramuscular injections, perianal trauma, and surgery. Unlike adult cases, children presenting with necrotizing soft tissue infections are more likely to be immunocompetent and without underlying chronic illnesses. Although rare in children, familiarity with the clinical manifestations of necrotizing soft tissue infections is essential for early diagnosis and surgical debridement, as significant mortality is associated with advanced disease.